The effectiveness of teacher performance in improving the learning outcomes of aqidah akhlak in Madrasah Aliyah Al-Manshury Sungai Bakau Besar Laut: EFEKTIVITAS KINERJA GURU DALAM MENINGKATKAN HASIL BELAJAR AQIDAH AKHLAK DI MADRASAH ALIYAH AL-MANSHURY SUNGAI BAKAU BESAR LAUT - Sumiyati, Sumiyati (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2023)
The objectives to be achieved by the author in compiling this article are explained as follows: Analyzing learning outcomes and teacherperformance in improving learning outcomes in Islamic religious education, especially the Aqidah Akhlak subject at Madrasah AliyahAl-Manshury Sungai Bakau Besar Laut. The approach used in this research is a qualitative descriptive approach. Because this researchactivity will produce descriptive data in the form of written or spoken words from people and observable behavior. Based on theresearch results, it can be concluded: (1) PAI learning outcomes, especially Aqidah Akhlak subjects at Madrasah Al-Manshury SungaiBakau Besar Laut are currently still in the below average category and even learning outcomes have decreased overall in every domainof student success. (2 ) in improving the effectiveness of teacher performance at Madrasah Aliyah Al-Manshury Sungai Bakau BesarLaut using various methods including: Attending workshops, Attending special PAI teacher training, Attending K-13 teacher training,in this way the implementation of the learning process becomes more focused and results in increased results study quite well.Key words: Effectiveness, Teacher Performance, Learning Outcomes and Moral Aqidah